Caleb Coppin: capstone - Coppin, Caleb, artist (Colorado State University. Libraries, 2024)
The artist's statement: My design work presents concepts in a refreshing and efficient manner. By mixing classic graphic design concepts with new techniques including 3D rendering, I provide clients and consumers alike with fun yet balanced designs. My practice incorporates 3-dimensional aspects in order to imbue a sense of physicality that is often lost in the digital age into my designs. Concurrently, I take advantage of these tools to envision designs not possible with traditional techniques, thereby pushing the boundaries of the design process. Conversely, I utilize design techniques outside of the computer as a way to incorporate a physical artistic practice while honoring previous generations of designers and maintaining reverence of their processes. By drawing, sculpting, and compositing in the physical world, I conserve the spirit of graphic design while anchoring my work outside of the digital landscape in order to furnish my work with a human touch.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design